Impacto da obesidade e cirurgia bariátrica nos parâmetros farmacocinéticos da amoxicilina - Rocha, Marina Becker Sales (2017)
Obesity and bariatric surgery may affect pharmacokinetic parameters that guarantee the success of a antibiotic therapeutic treatment. The objective of this study was to evaluate the impact of obesity and bariatric surgery on the pharmacokinetic parameters of amoxicillin. This was a randomized clinical trial, open-label, single-dose, with two periods of treatment in which participants (obese subjects who underwent bariatric surgery gastric bypass Roux-en-Y) received 500mg of amoxicillin orally. The concentration of amoxicillin was determined by using the HPLC-MS/MS method in eleven blood samples, collected at predetermined times of each participant. The groups were composed of 18 obese participants (5 male and 13 female, mean age of 39 years ± 7.6 years and mean body mass index (BMI) of 46.54 kg/m2 ± 4.7 kg/m2). 8 subjects underwent Roux-en-Y bypass bariatric surgery (4 men and 4 women, mean age 40.4 years ± 8.9 years, mean BMI of 39.82 kg/m2 ± 3.32 kg/m2). Previous data from 24 non-obese subjects were used as control (non-obese group - 12 males and 12 females, mean age 26.8 years ± 7.37 years and mean BMI of 23.73 kg/m2 ± 2.88 kg/m2). Compared with the control group, there was a reduction in AUC0-last and Cmax and an increase in T1/2 (P=0.0016) in the obese and obese who underwent bariatric surgery groups. When comparing participants before and after bariatric surgery, there was a statistically significant increase in AUC0-last and Cmax. No correlation was found between amoxicillin absorption, body mass index and percent weight loss. The modifications found in the pharmacokinetic parameters suggest that obese individuals have a substantially reduced absorption of amoxicillin and that this absorption rises after bariatric surgery.